Longitudinal Cell Tracking and Simultaneous Monitoring of Tissue Regeneration after Cell Treatment of Natural Tendon Disease by Low-Field Magnetic Resonance Imaging - Dagmar Berner; Walter Brehm; Kerstin Gerlach; Claudia Gittel; Julia Offhaus; Felicitas Paebst; Doreen Scharner; Janina Burk (Stem Cells International)
Treatment of tendon disease with multipotent mesenchymal stromal cells (MSC) is a promising option to improve tissue regeneration. To elucidate the mechanisms by which MSC support regeneration, longitudinal tracking of MSC labelled with superparamagnetic iron oxide (SPIO) by magnetic resonance imaging (MRI) could provide important insight. Nine equine patients suffering from tendon disease were treated with SPIO-labelled or nonlabelled allogeneic umbilical cord-derived MSC by local injection. Labelling of MSC was confirmed by microscopy and MRI. All animals were subjected to clinical, ultrasonographical, and low-field MRI examinations before and directly after MSC application as well as 2, 4, and 8 weeks after MSC application. Hypointense artefacts with characteristically low signal intensity were identified at the site of injection of SPIO-MSC in T1- and T2∗-weighted gradient echo MRI sequences. They were visible in all 7 cases treated with SPIO-MSC directly after injection, but not in the control cases treated with nonlabelled MSC. Furthermore, hypointense artefacts remained traceable within the damaged tendon tissue during the whole follow-up period in 5 out of 7 cases. Tendon healing could be monitored at the same time. Clinical and ultrasonographical findings as well as T2-weighted MRI series indicated a gradual improvement of tendon function and structure.